ANALISIS PELUANG PENGHEMATAN ENERGI LISTRIK GEDUNG JURUSAN TEKNIK ELEKTRO DAN TEKNOLOGI INFORMASI FAKULTAS TEKNIK UNIVERSITAS GADJAH MADA 2011 - , M. Zaky Zaim Muhtadi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Electrical energy savings become important for the community to reduce energy consumption. Some ways that can be done is the equivalent replacement of components that have better efficiency (retrofitting), upgrading of technology equipment and energy-saving behavioral habituation. In this study the calculation of the acquisition of savings that can be obtained by performing the equivalent replacement of components in air conditioning system and lighting system. Moreover, questionnaire was also conducted in this study to get the response from the people in JTETI-FT-UGM about the saving of electrical energy consumption. The results obtained from this study is that there is on average 5.252,415 kWh (22,4%) per month electrical energy savings opportunities in the air conditioning system by replacing refrigerant of freon into musicool. The, the electrical energy savings opportunities could also be obtained from the lighting system for about 2.320,318 kWh (20,8%) per month by replacing electronic ballasts and fluorescent lamps. The questionnaire indicate that the behavior of respondents in JTETI-FT-UGM against the savings in the consumption of electrical energy is in the category of good. While the time required for return on investment is 12 months in the air conditioning system and 76 months in the lighting system.